2017
DOI: 10.1177/0269881117724749
|View full text |Cite
|
Sign up to set email alerts
|

Roman high and low avoidance rats differ in their response to chronic olanzapine treatment at the level of body weight regulation, glucose homeostasis, and cortico-mesolimbic gene expression

Abstract: Olanzapine, an antipsychotic agent mainly used for treating schizophrenia, is frequently associated with body weight gain and diabetes mellitus. Nonetheless, studies have shown that not every individual is equally susceptible to olanzapine's weight-gaining effect. Therefore, Roman high and low avoidance rat strains were examined on their responsiveness to olanzapine treatment. The Roman high avoidance rat shares many behavioral and physiological characteristics with human schizophrenia, such as increased centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Quantity and chemical purity of RNA and cDNA were assessed using Nanodrop 2000 spectrophotometer (Thermo Fisher Scientific). mRNA expression was measured using real time polymerase chain reaction (RT-PCR) according to a protocol previously described (63). The RT-PCR was performed in triplicates by using validated UCP-1 primers (forward primer CAAAAACAGAAGGATTGCCGAAA, reverse primer TCTTGGACTGAGTCGTAGAGG), with housekeeping gene RPL13A, SYBR green and the CFX96 qPCR (Bio-Rad, Veenendaal, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Quantity and chemical purity of RNA and cDNA were assessed using Nanodrop 2000 spectrophotometer (Thermo Fisher Scientific). mRNA expression was measured using real time polymerase chain reaction (RT-PCR) according to a protocol previously described (63). The RT-PCR was performed in triplicates by using validated UCP-1 primers (forward primer CAAAAACAGAAGGATTGCCGAAA, reverse primer TCTTGGACTGAGTCGTAGAGG), with housekeeping gene RPL13A, SYBR green and the CFX96 qPCR (Bio-Rad, Veenendaal, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to vehicle-treated rats, body weight, blood glucose, and dopaminergic receptor expression in the cortico-mesolimbic system were higher in the olanzapine-treated Roman high-avoidance rats; in contrast, the Roman low-avoidance rats showed no differences in these measures. The discrepancy was due to the Roman high-avoidance rats having elevated central dopaminergic sensitivity, which indicated that dopamine receptor expression is related to olanzapine-induced weight gain (Evers et al., 2017). The serotonin 2C receptor has been implicated in many neurological and biological processes, including the regulation of food intake, body weight, and glucose metabolism.…”
Section: Antipsychotics and The Gut-brain Axismentioning
confidence: 99%
“…For example, a head-to-head meta-analysis reported that olanzapine causes the highest amount of weight gain 4. Additionally, there is ample evidence showing that it is likely that a complex biological mechanism is involved5 and that neuroendocrine alternation may play an important role in olanzapine-induced weight gain 6,7…”
Section: Introductionmentioning
confidence: 99%